Learning Models for Enhancing Science Literacy in Elementary Schools: Evidence from Indonesia - Ika Candra Sayekti; Anatri Desstya; Murfiah Dewi Wulandari; Aqthora Sulthonia; Riska Yulia Ayu Lestari; Badra Intan Mei Alviani; Fuad Naufal Nasik; Nur Amalia (International Journal of Learning Reformation in Elementary Education, 2026)
Scientific literacy serves as a critical foundation for cultivating critical thinking from an early age; however, instructional approaches that contextually accommodate diverse student characteristics remain limited, particularly at the elementary level. Therefore, this study aims to analyze the urgency of an innovative instructional model that strengthens science literacy among elementary school students. Employing a Design-Based Research (DBR) approach, this study is limited to the initial phase of problem identification and analysis. The research subjects comprised 16 elementary school teachers and 111 students across five districts in Surakarta, Indonesia. Data were collected through in-depth interviews, questionnaires, and an extensive literature review. The data analysis process involved data reduction, data display, and conclusion drawing. Source and methodological triangulation were applied to ensure data validity. The findings indicate that the integration of ethnoscience into science learning through a differentiation approach to significantly improve science literacy among elementary school students is needed.